Evaluation of awake bruxism behaviour with ecological momentary assessment (EMA) and its impact in muscle sensitivity tenderness and endogenous analgesia - Flores, Dyanne Adenea Medina (2020)
The aim of this study was to evaluate awake bruxism (AB) behaviors for one week in a sample of healthy young adults using an ecological momentary assessment (EMA) and the relationship of different AB behaviors with muscle tenderness and pain modulation (CPM) Methods: One hundred and twenty-two healthy postgraduate students were given a smartphone application that sends 10 alerts at random intervals every day, for one-week. Subjects had to report in real time what represented their current condition between these options: Relaxed jaw muscles, teeth contact, teeth clenching, teeth grinding and jaw bracing. Before the first day of alerts, the subjects also underwent recordings of the masticatory muscles pressure pain threshold (PPT) and the paradigm of conditioned pain modulation (CPM). The PPT recording was repeated in the last day of study. Results: Data were considered valid if compliance was of at least 60% of responses. The total compliance was of 75.9%. The average frequency of relaxed jaw muscles was 54.5%, 29.4% for teeth contact, 5.8% for jaw bracing, 9.7% for teeth clenching and 0.6% for teeth grinding. Teeth contact was found to be the most prevalent behaviour, 69% of participants showed at least one bruxism behaviour during the one-week evaluation period. Any significant gender difference was detected on the sample. The PPT values were within the normality parameters, for the anterior temporalis, 2.52 kg/cm2 and 2,26 kg/cm2 for right and left. The masseter muscle presented a pain threshold of 1.93 kg/cm2 and 1.84kg kg/cm2 for the right and left side, respectively. Statistically significant difference (p>0.000) were noted on CPM test with the difference between the PPT before (2.5 +- 1.07) and after (2.9 +- 0.96) the cold-water immersion, demonstrating a positive modulation on these young healthy patients. Conclusion: The most prevalent behavior was the teeth contact with an average frequency of 29.4%, where 69.6% of the participants presented at least once this behavior. AB is not an important factor of masticatory muscle tenderness on the orofacial pain area in young healthy adults. No association was found between AB behaviors with masticatory muscle tenderness and endogenous analgesia.